2017
DOI: 10.1007/s00423-017-1608-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for morbidity after appendectomy

Abstract: Based on our findings, surgical delay in the case of appendicitis and operation at night did not increase the risk for postoperative complications. However, the mean waiting time was less than 12 h and patients aged 70 years or older were at a higher risk for postoperative complications. Furthermore, for the subgroup of patients with complicated appendicitis, the time interval to surgery had a significant influence on the occurrence of postoperative complications. Therefore, the contemporary operation dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 24 publications
7
38
2
3
Order By: Relevance
“…While our complication rates in the non-pandemic period were similar to the studies in the literature, the rate of complications was higher during the pandemic period [8,9]. The high level of postoperative wound infection and pneumonia during this period is noteworthy.…”
Section: Discussionsupporting
confidence: 87%
“…While our complication rates in the non-pandemic period were similar to the studies in the literature, the rate of complications was higher during the pandemic period [8,9]. The high level of postoperative wound infection and pneumonia during this period is noteworthy.…”
Section: Discussionsupporting
confidence: 87%
“…Perhaps the emphasis should not rely (solely) on intraoperative findings, but on more quantifiable variables, such as serum C‐reactive protein and white blood cell count. Several radiological and laboratory factors have been associated with adverse outcomes after appendicectomy. A combination of these and intraoperative findings may result in more consistent postoperative management.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Lasek et al, it was stated that conversion to open surgery had no effect on postoperative morbidity (17) . In the study of Andert et al, postoperative morbidity was observed more frequently in conversion from laparoscopy and it was found to be a risk factor for the development of morbidity in multivariate analysis (27) . In this study, conversion was found to be a effective factor for morbidity, and in the multivariate analysis, and an effective risk factor in the development of postoperative morbidity.…”
Section: Discussionmentioning
confidence: 96%